EFFECT OF GAMMA IRRADIATION ON MORPHOLOGICAL CHARACTERISTICS AND ISOLATION OF CURCUMINOIDS AND OLEORESINS OF CURCUMA LONGA L. - S. Ilyas; S. Naz (Journal of Animal and Plant Sciences, 2014)
The present investigation was carried out to enhance the plant growth and production of curcuminoids and essential oils from turmeric (Curcuma longa) by gamma rays treatments. The plant samples of turmeric were collected from different regions of Kasur, Bannu and Faisalabad, Pakistan. The rhizomes were irradiated with 00 as control, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100Gy by cobalt 60 source. The germination response and percentage, plant height, average length, number and width of leaves, average root length and number, fresh and dry weights, rhizome weight, yields of essential oil and curcuminoids were affected with different levels of doses. Germination response was delayed at higher doses. Germination percentage was not significantly affected by increasing doses of gamma rays. The maximum plant height (70.8 cm) was attained at 60 Gy in plants collected from Kasur while higher doses showed reduction in heights. Lower doses have stimulatory effects on length, number and width of leaves where as higher doses had inhibitory effects. Maximum leaf length (47.6 cm) with 40 Gy and leaf number (8.8) at 70 Gy were recorded in samples of Kasur while highest leaf width was 14.6 cm at 50 Gy from plants of Faisalabad area. The rooting pattern of length showed increase gradually upto 60 Gy in Kasur plants and 70 Gy in Faisalabad while plants from Bannu gave maximum number of roots (6.2) at 70 Gy dose of gamma rays. Fresh and dry weights of plants were 75.0g and 53.0g respectively at 50 Gy with plants of Kasur. Rhizomes of plants from Kasur gave 0.73% yield of essential oil at 50 Gy as compared to non-irradiated (0.31%). Similarly yield of curcuminoids were also increased (12.4%) at 60 Gy in plants collected from Kasur.
Keywords: Turmeric rhizome; curcuminoids; gamma rays; germination percentage; essential oil and Curcuma longa